2020
DOI: 10.3390/molecules25051226
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Optimization of the Ultrasonic Extraction Method and Determination of the Antioxidant Activities of Hydroxysafflor Yellow A and Anhydrosafflor Yellow B from Safflower Using a Response Surface Methodology

Abstract: An evaluation of the ultrasonic extraction process and the antioxidant activities of hydroxysafflor yellow A (HSYA) and anhydrosafflor yellow B (AHSYB) from safflower are presented herein. Using response surface methodology (RSM), based on a four-factor-three-level Box–Behnken design (BBD), the extraction parameters, namely, temperature, extraction time, solvent-to-material ratio, and extraction power, were optimized for maximizing the yields of HSYA and AHSYB. The maximum yield was obtained at a temperature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 51 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Adeq Precision of 32.296 indicated an adequate signal. The coefficient of variation (CV) was selected to assess the predicted model reproducibility, which was obtained by calculating the ratio of the standard error to the mean value [ 30 ]. The CV of 1.52% suggested that the predicted model has great reproducibility.…”
Section: Resultsmentioning
confidence: 99%
“…Adeq Precision of 32.296 indicated an adequate signal. The coefficient of variation (CV) was selected to assess the predicted model reproducibility, which was obtained by calculating the ratio of the standard error to the mean value [ 30 ]. The CV of 1.52% suggested that the predicted model has great reproducibility.…”
Section: Resultsmentioning
confidence: 99%
“…As a comprehensive mathematical and statistical method, RSM has been applied to optimize multiple factors [30][31][32], and BBD is a traditional method that is used in the experimental design [33,34]. In the article, the factors of limewater concentration, processing time and solvent volume were listed to optimize the technology of LCSS based on BBD.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo and in vitro studies have shown that SY has significant effects in alleviating CCVDs, including the prevention of atherosclerosis and thrombosis, and as a cardioprotective and neuroprotective. Moreover, the closely related anti-oxidant [ 39 ], anti-inflammatory [ 40 ], and neuroprotective effects [ 41 ] play a role in the prevention and treatment of CCVDs.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%